Pengembangan Desain Kemasan Makanan Ringan Oleh-Oleh Khas Pasar Bengkel Serdang Bedagai - Ilyas Ali Rangkuti; Daulat Saragi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The background in this study is that the Serdang Bedagai Bengkel Market traders do not understand the management of packaging design with design designers, therefore the souvenirs sold are less attractive and look less hygienic. This research was conducted with the aim of helping traders to develop good packaging designs. The population taken in this study is food packaging design with a total population of 15 packaging designs. The samples taken in this study were 6 designs of packaging for snacks typical of Pasar Bengkel. Samples were taken using purposive sampling technique, with a packaging design population consisting of 15 packaging designs and in this study the researchers used the R&D method (Level 3), namely research and testing to develop existing products, this aims to develop designs using the principle of form. , materials, colors and typography on light packaging designs typical of Serdang Bedagai Bengkel Market. The results of research on the development of 6 packaging designs from the use of shapes, materials, typography and colors have all been declared feasible and achieved the values expected by the researchers. All the results of the development of packaging designs look more attractive, hygienic, luxurious, neat, clean and have economic value.